Non-Isolated DC–DC Power Converter With High Gain and Inverting Capability - Mohammad Meraj (16855401) (2021)
As the voltage gain of converter increases with the same ratio, the current gain also increases, this increase in current gains will affect the size of the input and the output capacitor. To reduce the ripple in the input current with simultaneous decreasing the input current ripple, a novel current fed interleaved high gain converter is proposed by utilizing the interleaved front-end structure and Cockcroft Walton (CW)-Voltage Multiplier (VM). The “current fed” term is used because, in proposed circuitry, all the capacitors of CW-VM are energized by a current path via inductors of the interleaved structure. The proposed converter can be applied as an input boost up the stage for low voltage battery energy storage systems, photovoltaic (PV) and fuel cell (FC) based DC-AC applications. The anticipated topology consists of the two low voltage rating switches. The main benefits of the anticipated converter configuration are the continuous (ripple free) input current, high voltage gain, reduced switch rating, high reliability, easy control structure and a high percentage of efficiency. The proposed converter's working principle, mathematical based steady-state analysis, and detailed component design are discussed. The parasitic of the components has been considered in the analysis to show the deviation from the ideal cases. A detailed comparison with the other available converters is presented. The experimental results of the 300W prototype are developed to confirm the performance and functionality of the anticipated DC-DC converter. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3074459